Human gait energy harvesting through decoupled suspended load backpacks. (May 2022) - Sriramdas, Rammohan; Cruz, Ricardo; Garcia, Anthony J.; Sharpes, Nathan L.; Priya, Shashank
Highlights: Decoupled backpack generates energy from the pack-mass suspended only on springs. Power and efficiency derivation for semi-coupled, decoupled and coupled backpacks. Coupled and semi-coupled harvester response is verified using Simulink models. Experimental coupled backpack harvesters indicated high normalized force. Efficiency of semi-coupled and decoupled backpacks is higher than coupled backpack. Abstract: Harvesting energy from human motion has the potential to power wearable sensors and low power portable systems. Here, a backpack harvester that generates electrical energy by suspending the pack-mass only on springs is demonstrated. In this mechanism, the relative motion between a fixed frame (relative to the body) and a suspended frame winds a torsional spring that serves as a mechanical reservoir in one-half of the oscillation cycle (one walking step). In the second half cycle, the stored energy is released to the generator. This approach eliminates the damping force from the generator on the human bearing the load. As the load is suspended on springs and does not directly drive the generator, the proposed system results in a decoupled harvester. Experimental results demonstrate that the output power generated from the decoupled harvester is 65% of that obtained from a semi-coupled harvester with 52% smaller backpack displacements and oscillatory forces. The decoupled and semi-coupled backpack harvesters achieved 53% and 45% efficiency at 1.4 m/s walking speed compared to 34% efficiency in a fully coupled harvester. This demonstrates significant advancement towards developing decoupled backpack energy harvesters that suspend pack-mass only on springs.